TEN COMMANDMENTS OF BUDDHISM AND ISLAM (A COMPARATIVE REVIEW) - Hafiz Muhammad Ibrar Ullah; Hashmat Begum; Samina Begum; Dr Fatima; Muhammad Yaseen; Muhammad Ayaz (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The statement Islam is derived from seen laam meem Salama. It means to survive, to be safe, to reconcile, and to find and provide peace and security. It also means giving peace and security to other people and protecting something. Similarly, Buddhism is one of the world’s religions, while some scholars have called Buddhism a philosophy rather than a religion. The principle of organization of this religion is to wear yellow clothes, shave one’s head, keep one’s head covered, etc. Raja Ashoka’s services in the development of Buddhism are unforgettable, hence it is called "Buddha Sani". In this selected study, the ten commandments of Buddhism have been compared with Islam.